Clinical and microbiological characteristics of bacterial infections in patients with cirrhosis. A prospective cohort study from Argentina and Uruguay - Vazquez, Carolina (2023)
Introduction and Objectives: there is insufficient data regarding bacterial infections in patients with cirrhosis to support recommendations for empiric antibiotic treatments, particularly in Latin America. This study aimed to evaluate bacterial infection's clinical impact and microbiological characteristics, intending to serve as a platform to revise current practices. Materials and Methods: multicenter prospective cohort study of patients with cirrhosis and bacterial infections from Argentina and Uruguay. Patient and infection-related information were collected, focusing on microbiology, antibiotic susceptibility patterns, and outcomes. Results: 472 patients were included. Spontaneous bacterial infections and urinary tract infections (UTIs) were registered in 187 (39.6%) and 116 (24.6%) patients, respectively, representing the most common infections. Of the 256 culture-positive infections, 103 (40.2%) were caused by multidrug-resistant organisms (reaching 50% for UTI), and 181 (70.7%) received adequate initial antibiotic treatment. The coverage of cefepime and ceftriaxone was over 70% for the empirical treatment of community-acquired spontaneous infections, but ceftazidime´s coverage was only 40%. For all UTI cases and for healthcare-associated or nosocomial spontaneous bacterial infections, the lower-spectrum antibiotics that covered at least 70% of the isolations were imipenem and meropenem. During hospitalization, a second bacterial infection was diagnosed in 9.8% of patients, 23.9% required at least one organ support, and 19.5% died. Conclusions: short-term mortality of bacterial infections in patients with cirrhosis is very high, and a high percentage were caused by multidrug-resistant organisms, particularly in UTIs. The information provided might serve to adapt recommendations, particularly related to empirical antibiotic treatment in Argentina and Uruguay. The study was registered in Clinical Trials (NCT03919032).